2020
DOI: 10.1038/s41598-020-77771-y
|View full text |Cite
|
Sign up to set email alerts
|

Risks of forgotten double-J ureteric stents after ureterorenoscopic lithotripsy in Taiwan: a nationwide population-based study

Abstract: Delayed double-J ureteric stent (DJ) removal may cause severe morbidity. We aimed to identify high-risk patients for forgotten DJs to prevent iatrogenic injury and improve safety. Data of patients with DJs placed after ureterorenoscopic lithotripsy (URSL) between 2000 and 2013 from the National Health Insurance Database in Taiwan were included. Forgotten DJs were defined as indwelling DJs for > 6 months after URSL, which is approximately two times longer than the expiratory duration. Age at stenting, sex, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…15 Previous studies revealed older people were at greater risk of forgetting ureteral stents. 16,17 Application of this interactive counselling program provided older adults with more time to understand the information provided by the medical staff, even after discharge, which is advantageous and timeeffective for both patients and medical staff. Interestingly, we noticed that younger patients and those who used the interactive counselling program reported more severe gross haematuria.…”
Section: Discussionmentioning
confidence: 99%
“…15 Previous studies revealed older people were at greater risk of forgetting ureteral stents. 16,17 Application of this interactive counselling program provided older adults with more time to understand the information provided by the medical staff, even after discharge, which is advantageous and timeeffective for both patients and medical staff. Interestingly, we noticed that younger patients and those who used the interactive counselling program reported more severe gross haematuria.…”
Section: Discussionmentioning
confidence: 99%